Geosite Potential Assessment Using the Modified Geosite Assessment Method (M-GAM) in North Musi Rawas Regency - Lee, Jason; Setiawan, Budhi (Jambura Geoscience Review, 2026)
This study assesses the geosite potential of two emerging geotourism locations Rayo Lake and Sosokan Waterfall in North Musi Rawas Regency using the Modified Geosite Assessment Method (M-GAM). The research aims to address the limited empirical application of M-GAM in developing geotourism regions of Indonesia, thereby filling an important methodological and regional gap. The assessment incorporates expert and visitor perceptions to evaluate Main Values (MV) and Additional Values (AV) across geological, educational, and touristic criteria. Field surveys and questionnaire-based evaluations were conducted with 22 experts and 55 visitors. The results show that Rayo Lake attained a high MV score and a moderate AV score, placing it in quadrant Z33, indicating strong geological significance supported by adequate visitor-related attributes. In contrast, Sosokan Waterfall was positioned in quadrant Z22, reflecting moderate performance in both MV and AV categories, primarily constrained by limited infrastructure and accessibility. These findings confirm that geological attributes alone are insufficient to elevate geosite readiness without parallel development of visitor-oriented facilities. The study’s novelty lies in providing the first M-GAM-based comparative assessment for geosites in North Musi Rawas, offering actionable insights for regional planning. Strengthening infrastructure, interpretive media, and accessibility is recommended to optimize geotourism development strategies.